Beyond biology: the impact of marital status on survival of patients with adrenocortical carcinoma - Klaassen, Zachary (Int Braz J Urol, 2015)
PURPOSE: To analyze the association of marital status and survival of patients with ACC using a population-based database. MATERIAL AND METHODS: Patients with ACC were abstracted from the Surveillance Epidemiology and End Results (SEER) database from 1988-2010 (n=1271). Variables included marital status (married vs single/divorced/widowed (SDW)), gender, age, race, tumor (T) and node (N) classification, receipt of surgery, and SEER stage. Statistical analysis was performed using Cox proportional hazard models to generate hazard ratios and 95% confidence intervals. RESULTS: There were 728 (57.3%) females and median age was 56 years (IQR 44-66). Patients who were alive were more frequently married (65.6% vs 61.6%, p=0.008), female (61.1% vs 58.0%, p=0.001), younger (median 51 vs 57 years, p=0.0001), submitted to adrenalectomy (88.6% vs 63.8%, p<0.0001), and more favorable SEER stage (localized-64.9% vs 29.9%; regional–25.1% vs 30.1%; distant 4.8% vs 31.5%, p<0.0001) compared to patients dead of disease (DOD). On multivariable analysis, factors significantly associated with all-cause mortality were SDW status (HR 1.28, 95% CI 1.091.51), age, non-operative management, and N+ disease. Risk factors for disease-specific mortality included SDW status (HR 1.30, 95% CI 1.07-1.56), age, non-operative management, T-classification, and N+ disease. CONCLUSIONS: Marital status is significantly associated with survival in patients with ACC. Our results suggest that the decreased survival seen among SDW individuals highlights an area for further research and needed intervention to reduce disparity.